Perlindungan Hukum Bunga Edelweis di Kawasan Taman Nasional Gunung Gede Pangrango Berdasarkan Undang-Undang Nomor 5 Tahun 1990 Tentang Konservasi Sumber Daya Alam Hayati Dan Ekosistemnya - Erwin Owan Hermansyah Soetoto; Monica Graicila (KRTHA BHAYANGKARA, 2022)
This article describes and examines the problem how are the efforts to protect Edelweiss Flowers in the Gunung Gede Pangrango National Park area based on Law Number 5 of 1990 concerning Conservation of Biological Natural Resources and Their Ecosystems. With the background of widespread destruction of ecosystems by human ignorant hands, the author sees from the side of biological life (plants) within the scope of conservation areas, which is stated in UUKH Number 1990. It is necessary to give an understanding, especially on the survival of Edelweiss Flowers which are included in conservation areas, as well as protection in particular written in the Regulation of the Minister of Environment and Forestry Number P.106/MENLHK/SETJEN/KUM.1/12/2018 concerning Protected Types of Plants and Animals. Because the myth of the eternal flower that is very much loved by mountain climbers to cause the act of picking and destroying the Edelweiss flower plant, and has a selling value in the eyes of the people around the area, therefore the existence of this Edelweiss flower needs to be reconsidered, it is necessary to enforce a protection against the flower. Edelweiss.